Analisis Kesulitan Belajar Mahasiswa dalam Menyelesaikan Soal Matematika Ekonomi pada Materi Fungsi Permintaan dan Fungsi Penawaran ditinjau dari Kemampuan Pemecahan Masalah Matematis - Puspaningrum, Cici (Economic Development Progress, 2024)
The aim of this research is to analyze and describe the difficulties experienced by students in solving economic mathematics questions on demand function and supply function material in terms of mathematical problem solving abilities. This research is a qualitative descriptive research with a case study approach. The subjects in this research were 35 first semester Management Study Program students at STIE Bina Karya Tebing Tinggi. Data collection was carried out through tests and interviews. The test questions are in the form of a description of 2 questions to determine the level of the subject's mathematical problem solving ability. Meanwhile, interviews were conducted in a structured manner based on guidelines that had been created, with the aim of finding the subject's level of difficulty through data obtained from the subject's answers during the written test. The data obtained was then analyzed based on Milles and Hubermen's analysis flow, namely data reduction, data presentation, and conclusions or data verification. The results obtained from this research are that subjects who have a KMT level tend not to have difficulty in solving questions. At the KMS level, subjects tend to have difficulty applying principles and solving verbal problems. At the KMR level, subjects tend to experience difficulties in solving questions, namely understanding concepts, applying principles and verbal problems.